Seasonal variations in the profundal Chironomidae (Diptera) assemblage of a subarctic lake. - Mousavi, Seyed Karim; Amundsen, Per-Arne (Boreal Environment Research Publishing Board, 2012)
Zoobenthos samples were collected over a 12-month period in the profundal zone of the subarctic Fjellfrøsvatn, a lake in northern Norway. Chironomid larvae numerically dominated the profundal zoobenthos and their mean density decreased with increasing depth. Procladius (Holotanypus) sp. A, Mesocricotopus thienemanni, Psectrocladius (Mesopsectrocladius) sp. and Heterotrissocladius subpilosus exhibited the highest densities at the depth of 20 m, whereas H. subpilosus dominated the chironomid assemblage at 30–40 m. At 20-m depth, the chironomid density was highest in June, decreased towards autumn, and was relatively stable during the ice-covered period. The peak density in June was mainly related to a strong seasonal pattern in the density of Heterotrissocladius maeaeri and M. thienemanni. At 30–40-m depth, no significant seasonal variations in total density of chironomid larvae were observed, although the density of H. subpilosus exhibited a significant seasonal peak in winter. Larval instar groups of H. subpilosus were identified from a classification based on head capsule width. The profundal dwelling H. subpilosus were hemivoltine, having predominantly a two-year life cycle.